(untitled) (American Journal of Islam and Society, 2016)
Numerous conferences have been held on themes related to the Islamic golden age of science during the mid-eighth to thirteenth centuries. But the event reported here is the “event of events,” so to say. The United Nations declared 2015 the International Year of Light and Light-based Technologies (IYL-2015) to stimulate global interest in light-related sciences and technologies. The IYL-2015 partnership, formed in 2010, is a cross-disciplinary educational and outreach project with over 100 partners from more than 90 countries, accompanied by UNESCO’s International Basic Sciences Program. UNESCO’s executive board adopted this resolution during its October 2012 session; the UN declared IYL-2015 in December 2013. The year 2015 marks numerous anniversaries in the field of optics. The oldest among these is the 1000th anniversary of the appearance of Ibn al- Haytham’s (965-1040) encyclopedic Book of Optics (Kitāb al-Manāẓir) by the Arab scientist. Ibn al-Haytham became a central figure in the documents submitted to UNESCO’a board and eventually the UN. The International ...